Clinical course for pancreatic necrosis and pancreatic pseudocysts due to severe acute or chronic pancreatitis - Stefano Fusco; Greta M. Hanke; Karsten Büringer; Lisa Minn; Gunnar Blumenstock; Ulrike Schempf; Martin Götz; Nisar P. Malek; Dörte Wichmann; Christoph R. Werner (Therapeutic Advances in Gastroenterology)
Background: The acute and chronic pancreatitis (CP) can lead to severe complications like walled-off necrosis, large symptomatic pseudocyst or multiorgan failure. The treatment of these complications is multivariate and can differ from conservative, symptomatic treatment or minimal-invasive, endoscopic transgastral stenting to transgastral necrosectomy. Objectives: This study aims to analyse the clinical course for patients that develop local complications of severe pancreatitis. Design: This is a retrospective observational single-centre study on 46 patients with severe pancreatitis. Methods: In this retrospective single-centre study, 46 out of 474 inpatients from January 2014 to December 2020, who were treated because of an acute or CP, developed acute pancreatitis complications and could be included. We analysed and compared the clinical course of different treatments (lumen apposing metal stents, transgastral double pigtail stent, endoscopic retrograde cholangiopancreatography, operation, conservative treatment) and different complications (walled-off necrosis (WON), pancreatic pseudocyst (PPC)). Results: Forty-six patients developed an acute complication due to severe pancreatitis. Twenty-seven patients developed a WON, while 19 patients suffered from PPC. 48% of the whole cohort had an alcoholic aetiology of pancreatitis. 78% were treated with antibiotics, 48% suffered from infected pancreatitis and 22% needed intensive care treatment. WON patients more often had a longer hospitalization of more than 21 days. PPC patients were correlated with an alcoholic aetiology, whereas WON patients were inversely correlated with an alcoholic aetiology. Increased lactate dehydrogenase, lipase, and C-reactive protein levels as well as leucocyte count could be associated with a higher probability to exhibit a WON instead of another local complication. The mortality rate was low with 7% in our study. Conclusion: WON and PPC differ in certain patients and laboratory characteristics such as aetiology, elevated laboratory values, antibiotic treatment or the duration of hospitalization. Invasive treatment is not required in all severe pancreatitis cases.